(3GdeLed aj GddZIs - (3GHf aGQS , CHh GdMSjf CMeO Hf aGQS Hf RcQjGA GdbRhjfj GdQGRj,J (B395 (3g` s ((3GHQGgje Hf ehSi Hf GdaQL GdHGHi GdeJCOH s)
(3ChdgG (B:s
(3jHOC HcJGH GdgeRI HGH GdGda s
(3BNQgG (B:s
(3jfJgi CKfGA HGH eG LGA Ydi CcKQ ef KdGKI CMQa Chdg UGO s
(3GdLRA GdChd hHYV GdKGfis
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs